Characteristics of high‐resolution esophageal manometry in children without dysphagia. Issue 2 (4th June 2021) - Kovacic, Karlo; Kern, Mark; Pawela, Louis; Shaker, Reza; Sood, Manu R.
Abstract: Background: The absence of high‐resolution esophageal manometry (HREM) norms in pediatrics limits the assessment of children with dysphagia. This study aimed to describe HREM parameters in a cohort of children without dysphagia. Methods: Children ages 9–16 years with a negative Mayo Dysphagia Questionnaire screen and normal histologic findings underwent HREM after completion of esophagogastroduodenoscopy. Ten swallows of 5 ml 0.45% saline boluses per subject were captured in supine position. Analyzed data included resting and integrated relaxation pressures (IRP) of lower (LES) and upper (UES) esophageal sphincters, peristaltic contractile integrals, transition zone (TZ) breaks, velocities, and lengths associated with proximal and distal esophagus. Key Results: 33 subjects (15 female) with mean (range) age 12.9 (9–16) years completed the study. Two of 330 analyzed swallows failed. The UES mean resting pressure, and its 0.2 s and 0.8 s IRPs were 48.3 (95% CI 12.9) mmHg, 2.9 (95% CI 1.9) mmHg, and 12.1 (95% CI 2.5) mmHg, respectively. The LES mean resting pressure and its 4 s IRP were 29.0 (95% CI 4.0) mmHg and 9.2 (95% CI 1.3) mmHg. The mean proximal (PCI) and distal (DCI) esophageal contractile integrals were 231 (95% CI 54.8) mmHg‐s‐cm and 1789.3 (95% CI 323.5) mmHg‐s‐cm, with mean TZ break 0.5 (95% CI 0.3) cm. Conclusions & Inferences: This is the first study to describe HREM parameters in children without dysphagia. Most of the reported measurements were significantly different and less variable from reported adult norms. This emphasizes the need for child‐specific catheters, norms, and protocols to define pediatric esophageal motility disorders. Abstract : Established and novel HREM parameters in the first prospective study of children without dysphagia. Most measurements were significantly different and less variable compared to adult established norms. ​